PENDIDIKAN KEIMANAN DI MADRASAH (Studi Strategi Pembinaan Akidah Islamiyah Di MA Pondok Pesantren Darul Fikri Ponorogo) - Katni . (Universitas Muhammadiyah Ponorogo, 2013)
The aspect of faith is still interesting to study, due to a lot of faith deviation by the islamic society in Indonesia. The islamic faith founding, therefore, needs the specific strategy bacause faith hold the central role of one?s relegion. In a religious concept, if a moslem has a wrong faith, it means his worship and charity will not be accepted by Allah SWT. This research aimed to describe the strategy of Islamic faith founding at Darul Fikri Boarding School of Ponorogo. In collecting the data, the researcher used in-depth interview, observation, and documentation. The research result showed three important points of the faith founding strategy, such as: (1) choosing the reference which was appropriate to Qur?an and Hadist. (2) coordinating the tauhid training (daurah) for teachers and students. Generally, it could be concluded that the teachers hold the important role in the faith founding, that they should have a better faith before teaching it to their students and also the students should get enough knowledge of faith. (3) creating an Islamic environment which would be unseparated system in the islamic faith founding and all islamic teaching.